"It's Just Constantly Having to Make a Ton of Decisions That Other People Take for Granted": Pregnancy and Parenting Desires for Queer Cisgender Women and Non-binary Individuals Assigned Female at Birth. Issue 2 (15th March 2021) - Carpenter, Emma; Niesen, Rachel
Abstract: As more queer cisgender women and gender-expansive individuals become parents, research must consider current barriers to family formation. This study used a modified grounded theory approach to conduct 22 semi-structured interviews aimed at understanding the role of queer identity in pregnancy desires and decisions among individuals assigned female at birth (AFAB) who identify as queer. Numerous individual, relationship, and structural factors informed pregnancy desires, the choice to seek pregnancy, and experiences with pregnancy. Supporting queer individuals in a range of pregnancy and parenting options is vital to fully recognizing queer individuals as participants in a fundamental human experience—family building.